Continuous Monitoring of Service Conditions of a Steel Storage Racking System. Issue 3 (3rd March 2020) - Castiglioni, Carlo A.; Drei, Alberto; Kanyilmaz, Alper
ABSTRACT: This paper presents the results of a continuous monitoring activity of a commercial steel pallet-rack. The first objective was to obtain the real history of the dynamic actions undergone by the rack under daily service conditions. The second objective was to evaluate the damping factors obtained during the most important dynamic shakes. Finally, the possibility of adopting these damping factors in the future standards has been discussed. The intensity and the number of cycles caused by the daily impacts shown in this study revealed also the importance of the fatigue phenomena.